Al-Khilâfah Menurut Rasyid Ridha (Studi Tafsir Al-Mannar) - Ahmad Danis (Universitas Darussalam Gontor, 2019)
Al-Khilafah was often viewed as an authoritarian system of leadership, moreover, it was often seen to force the people to follow the decision of leaders. This was because many people did not understand the true meaning of the “Khilafah”. Furthermore, the theologian difference argument about the term of “khilafah”. This article intended to present the interpretated of “khilafah” term according to Theologian. It was according to Muhammad Rasyid Ridha in al-Mannar’s interpretation which had a different view on “khilafah” term, which was viewed by interpretation of The Qur’an based on social conditions. After being reviewed and described using descriptive analytical methods, it found that some important points about the “khilahah” according to Rashid Ridha. The “khilafah” is a system that concern to aspects of Islamic law aimed to human beneficial such prephet, it was also called “khilafah” who maintained peace. It was also to creatthe benefit for the world and hereafter.